Association of Social Network Characteristics with Substance Use among College-Going Young Adults: A Cross-Sectional Study. Issue 2 (March 2023) - Pradeep Kumar P.C.,; Antony, Sojan; Murthy, Pratima; Thirumoorthy, A.; Philip, Mariamma
Background: Family members, peers, and significant others are part of a college student's social network. This cross-sectional study aimed to Assess substance use prevalence and patterns among college students, Compare the social network characteristics of substance users (SUs) and non-users (NUs), and Explore the association of social factors with substance use. Methods: The study involved 902 students from 11 Government and aided private degree colleges. Demographic and clinical data sheet, ASSIST, and Social Network Questionnaire were used to collect the data. Results: Prevalence of substance use was 26.9% and higher among males (21.5%). Alcohol (20%) and tobacco (15.5%) were the commonly used substances. SUs' network was composed of unmarried persons (p<0.002), male members (p<0.001), and friends (p<0.001) with substance use. In contrast, the NUs' network comprised parents (p<0.016) and siblings (p<0.001). NUs had a higher number of influential members in the network, whereas SUs had more closeness with members and received higher financial support (p<0.001). Participant's age (OR 1.27), family history of substance use (OR 2.46), parents' occupation (Business: OR 1.79, being employee in the government or industry: OR 1.76), and having three substance-using members in the network (OR .211) were found to be risk factors. Conclusion: Social network has an association with substance use among college students. Social-network-based interventions may benefit them.